Evaluation Analysis of Early Childhood Social Emotional Learning - Aulia, Putri; Sitorus, Ahmad Syukri (Universitas Islam Negeri Sumatera Utara, 2025)
Social emotional learning is one aspect of early childhood education that is important to evaluate. Learning evaluation aims to provide a clear picture of a child's development. This research aims to analyze early childhood social emotional learning evaluation activities. This research uses a descriptive qualitative approach by collecting data through interviews and observation. The data analysis used is thematic analysis. The results show that teachers use three assessment techniques, namely giving questions, observation based on direct events and art/Craft. Furthermore, in assessing children's social and emotional emotions, the teacher reports the assessment by describing the results of the assessment through a report card book which is carried out three times a semester to parents.